Literature Review and Bibliometric Mapping Analysis: Philosophy of Science and Technology Education - Dwi Fitria Al Husaeni; M. Munir (Indonesian Journal of Multidiciplinary Research, 2023)
The research objective is to conduct a literature review regarding the philosophy of science views on science and technology, especially in the field of Education. Bibliometric analysis was carried out through mapping visualization using VOSviewer. The research method is Systematic Literature Review (SLR). Bibliometric analysis mapping has 4 stages: data search, data processing, data mapping, and data analysis. The keywords used are "Philosophy of Science" AND "Technology" with a range of 2018 - 2022. The number of articles obtained was 184 articles. The number of articles used for the literature review is 10 articles. The results show that research development has decreased from 2018 to 2020 and has increased from 2020 to 2022. Philosophy of science in the field of science and technology has many opportunities in various fields and studies within the scope of science and technology. Issues related to the philosophy of science are still quite widespread, especially for Science, Technology, Engineering, and Math (STEM) students, due to the lack of confidence in STEM students in the philosophy of science. The link strength value of the connection between philosophy and science is stronger when compared to the connection between philosophy and technology. This means that more researchers are linking philosophical research to science than technology. This research is expected to be a consideration in determining the research theme to be carried out, especially those related to the field of philosophy of science.